2017
DOI: 10.1111/aos.13367
|View full text |Cite
|
Sign up to set email alerts
|

Objective and subjective outcomes of strabismus surgery in Graves' orbitopathy: a prospective multicentre study

Abstract: After strabismus surgery in GO patients, both the field of BSV and quality of life questionnaires increase. In approximately 30% of the patients, an additional strabismus surgery is performed. This second surgery significantly expands the field of BSV and the quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
(64 reference statements)
1
11
0
1
Order By: Relevance
“…This means that a sufficient precision can be achieved for these relatively small deviations (see BSV). Our results confirm that single muscle surgery has primarily a good prognosis in GO patients (Esser 1994;Esser & Eckstein 1999;Schittkowski et al 2004;Jellema et al 2017;Eckstein et al 2018). Much more complex is the situation for patients if single muscle surgery does not suffice: usually, there are two options, either to use implants or to weaken the contralateral antagonist.…”
Section: Surgical Resultssupporting
confidence: 79%
“…This means that a sufficient precision can be achieved for these relatively small deviations (see BSV). Our results confirm that single muscle surgery has primarily a good prognosis in GO patients (Esser 1994;Esser & Eckstein 1999;Schittkowski et al 2004;Jellema et al 2017;Eckstein et al 2018). Much more complex is the situation for patients if single muscle surgery does not suffice: usually, there are two options, either to use implants or to weaken the contralateral antagonist.…”
Section: Surgical Resultssupporting
confidence: 79%
“…In 2015, Jellema 11 reviewed the literature and suggested two factors that define strabismus surgical success: measurement of the field of binocular single vision (BSV) with the Goldman perimeter and QoL questionnaire. In 2017, Jellema 28 demonstrated that both field of BSV and QoL need to be measured to describe outcomes of strabismus surgery in patients with TED.…”
Section: Discussionmentioning
confidence: 99%
“…Jellema et al. () reported an increase in quality of life and binocular single vision after strabismus surgery; and a requirement of additional strabismus surgery in approximately 30% of the TAO patients. In our cohort, 14 patients (12%) were re‐operated within the 2 years.…”
Section: Discussionmentioning
confidence: 99%